Peningkatan Kemampuan Berhitung Anak Melalui Permainan Kartu Angka pada Anak Kelompok B RA Al Busyro Ngimbang Palang Tuban - Warni Warni (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to improve the numeracy skills of early childhood through the use of number card games. Numeracy is one of the basic competencies that is important to develop as a foundation for future mathematics skills. The method used in this study is game-based learning, where children are involved in interactive and fun number card playing activities. The subjects of this study were children aged 5-7 years at RA Al Busyro Ngimbang. The results of the study showed that the use of number card games can significantly improve children's numeracy skills, especially in the aspects of number recognition, addition, and simple subtraction. This game helps children understand basic mathematical concepts more naturally and without pressure, because the learning process is carried out in a fun and informal atmosphere. In addition, number card games can also increase children's motivation in learning mathematics, improve social skills through interaction with peers, and improve concentration and focus during the learning process. The conclusion of this study shows that number card games can be used as an effective learning strategy to improve the numeracy skills of early childhood. It is recommended for educators and parents to utilize this method in order to develop children's mathematical abilities more optimally.